The spatial variability of PM₂.₅ over Europe using satellite POLDER-3/PARASOL data - Bovchaliuk, A. (Advances in Astronomy and Space Physics, 2013)
The paper presents the results of the monthly mean PM₂.₅ analysis in the period from 2005 to 2013 over the Europe based on the connection between daily fine particle concentrations (PM₂.₅) by surface in-situ measurements in AIRBASE network and column aerosol optical thickness (AOT) derived from POLDER-3/PARASOL satellite sensor. The regression function between PM₂.₅ and AOT was derived from measurements done over Europe in the period from April to October 2007. Considering 749 match-up data points over 20 fine particle monitoring sites, we found that the POLDER-3/PARASOL derived AOT at 865 nm is correlated with collocated PM₂.₅ measurements with a correlation coeficient 0.62 (RMS = 3.26). According to the obtained linear regression PM2.5 = 73.4 × AOT865 + 9.6, a signi cant o set caused an introduction of the threshold of 0.01 in monthly mean AOT for assessment of PM₂.₅ based on satellite data. Therefore, only PM₂.₅ values larger than 10.3 µg/m³ can be obtained using this method. According to results the monthly mean PM₂.₅ in the period from 2005 to 2013 over the Europe is usually characterised by values less than 12 µg/m³ (classified as "good" by Air Quality Categories, AQC), but values ranging from 12 to 18 µg/m³ (classified as "moderate") are found in the densely populated and industrial areas, such as the Netherlands, Belgium, the Ruhr and Danube area, Northern Italy, Poland, Romania and Eastern Ukraine. Additionally, the maximum values of PM₂.₅ over Eastern Europe are observed during forest, peat and agricultural wildfires in May 2006 (15-21 µg/m³), April 2009 (14-18 µg/m³) and August 2010 (35-55 µg/m³, classi-fied as "unhealthy for sensitive groups"). An extended set of aerosol parameters including particle size distribution, complex refractive index, as well as parameters characterising aerosol particle shape and vertical distribution will be analysed in the future work.